ANALISIS SEBARAN RADIONUKLIDA PADA KONDISI NORMAL UNTUK REAKTOR AEC 1000 MW - Kuntjoro, Sri (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Analysis for radionuclide dispersion for the Atomic Energy Agency (AEC) 3568 MWth Power Reactor, equal to the 1000 MWe at normal condition has been done. Analysis was done for two piles that is separated by 500 m distance and angle of 90o one to other. Initial pace in doing the analysis is to determine reactors source term using ORIGEN2 and EMERALD NORMAL. computer code program. ORIGEN2 applied to determine radionuclide inventory emerged in the reactor. Hereinafter, by using Emerald Normal Computer code is calculated source term reaching the reactor stack. To analyze dose received by population is done by using PCCREAM computer code. Calculation done for one and two PLTN attached in site candidate of plants. The result showed is that the highest radionuclide release for one PLTN is at 1 km distance and to 9th zone toward ( 19.25o) and for two PLTN is at 1 km distance and to 10th zone toward (21.75o). Radionuclide which up to population through two pathsway that are foodstuff and inhalation. To foodstuff comes from radionuclide I-131, and the biggest passed from milk product with 53.40 % for one and also two PLTN . For inhalation pathway the highest radionuclide contribution come from Kr-85m is about 53.80 %. The highest total dose received by population is at 1 Km distance received by baby that is 4.10 μSi and 11.26 μSi for one and two PLTN respectively. Those result are very small compared to the maximum permition dose to population issued by regulatori body that is equal to 1 mSi.